Applying fuzzy interpretive structural modeling to evaluate responsible consumption and production under uncertainty - Wang, Liang (Animo Repository, 2018)
Purpose - The purpose of this paper is to adopt fuzzy interpretive structural modeling (ISM) to develop a precise evaluation framework and provide a theoretical basis for enhancing the understanding of responsible consumption and production (RCP) in academic and industrial fields. Design/methodology/approach - An integration of fuzzy set theory and ISM is proposed to maintain a higher level of consistency and reduce the uncertainty inherent in expert responses. Findings - RCP can be categorized into seven levels, which represent the driving power from higher to lower. The top aspect is management style; the remaining aspects are stakeholder management, regulation compliance, efficiency improvement, sustainable awareness, sustainable production and social responsibility. Research limitations/implications - This study attempts to integrate the triple bottom line (TBL) concept and corporate sustainability to develop a significant framework for evaluating RCP. Although the proposed aspects and criteria can be used to evaluate the Chinese construction industry, these may be insufficient for other industries. In addition, further discussion regarding important aspects and criteria is required to complete the theoretical basis. Practical implications - The results indicate that the top two criteria are establishing transparent communication channels and promoting managerial attitudes and behavior, which are followed by technology capabilities, organizational culture and stakeholder engagement. These five criteria play important roles when implementing RCP practices among Chinese construction firms. Originality/value - This study is the first to discuss RCP via an integration of the TBL concept and corporate sustainability. The framework developed herein provides a precise guideline for Chinese construction firms to improve their performance, and it also promotes the efficient use of resources via sustainable practices. © Emerald Publishing Limited.